Broad scale quantified flood risk analysis in the Taihu Basin, China. Issue 1 (22nd January 2013) - Yu, C.; Hall, J.W.; Cheng, X.; Evans, E.P.
Abstract A geographic information system (GIS)‐based analysis tool, the Taihu Basin Risk Assessment System (TBRAS), is developed to perform scenario analysis of future flood risk changes in the Taihu Basin. The TBRAS integrates modules of climate modelling, hydrological and hydraulic modelling, dyke reliability analysis, socioeconomic analysis, and damage assessment. The results indicate that the TBRAS can provide a broad‐scale simulation of the flooding processes and damage evaluation for the entire Taihu Basin. Future climate change by 2050 in precipitation alone can approximately result in four or five times of risk increase compared with the 2005 baseline risk. Socioeconomic changes alone can increase flood risk by four to six times. The paper reveals that, without any proactive responses, the combination of socioeconomic change, sea‐level rise, and other climate changes can substantially increase the overall flood risks to 15–37 times of the present situation. We therefore conclude that both structural and non‐structural measures for reducing flood risks are required and provide a set of response options for managing and adapting future flood risk changes.